The BAP31/miR-181a-5p/RECK axis promotes angiogenesis in colorectal cancer via fibroblast activation - Zhang, Qi; Wang, Changli; Li, Ruijia; Liu, Jingjing; Wang, Jiyu; Wang, Tianyi; Wang, Bing (Frontiers in Oncology, 2023)
BAP31 has been recognized as a tumor-associated protein and has largely been shown to promote metastasis in a variety of cancers. Cancer metastasis arises through multistep pathways, and the induction of angiogenesis is shown to be a rate-limiting step in the process of tumor metastasis. Accordingly, this study explored the effect of BAP31 on CRC angiogenesis by regulating the tumor microenvironment. First, exosomes from BAP31-regulated CRCs affected the transition of normal fibroblasts to proangiogenic CAFs in vivo and in vitro. Next, microRNA sequencing was performed to analyze the microRNA expression profile of exosomes secreted from BAP31-overexpressing CRCs. The results indicated that the expression of BAP31 in CRCs significantly altered the levels of exosomal microRNAs, such as miR-181a-5p. Meanwhile, an in vitro tube formation assay showed that fibroblasts with high levels of miR-181a-5p significantly promoted endothelial cell angiogenesis. Critically, we first identified that miR-181a-5p directly targeted the 3’UTR of RECK using the dual-luciferase activity assay, which drove fibroblast transformation into proangiogenic CAFs by upregulating MMP-9 and phosphorylation of Smad2/3. Conclusively, exosomes from BAP31-overexpressing/BAP31-knockdown CRCs are found to manipulate the transition of fibroblasts into proangiogenic CAFs by the miR-181a-5p/RECK axis.